Clinical significance and morphological analysis of the os subfibulare using radiologic assessment in patients with chronic lateral ankle instability. Issue 3 (14th September 2018) - Lee, Doo Jae; Lee, Dong Yeon; Lee, Jae Hee
Category: Ankle Introduction/Purpose: Although os subfibulare has been associated to various clinical problems in patients with chronic lateral ankle instability (CLAI), there are a few studies on the analysis of morphological characteristics of os subfibulare. The purpose of this study is to analyze morphologic characteristics of the os subfibulare and to evaluate the clinical significance of the os subfibulare in patients with CLAI. Methods: Among 252 patients who visited our training hospital with the symptom of lateral ankle instability for more than 1 year after sustaining ankle injury, 71 patients with os subfibulare who underwent magnetic resonance imaging (MRI) of the ankle were included in this study. For each patient, the simple radiologic assessment was also performed. The shape and size of ossicles were measured on a sagittal MR images. The location of the subfibular ossicle was classified into 3 zones by relation with the attachment site of the anterior talofibular ligament. The talofibular impingement, in which ossicles impinged to the talar articular surface. Results: The most common shape of ossicles was oval, and the most common site of ossicles was ATFL attach site. 61% of patients showed talofibular joint impingement on axial MR images, whereas 28 cases showed normal congruency of the talofibular joint. Forty-eight cases in 71 patients with CLAI had an enlarged fibular shape instead of a contralateral fibula on simple radiographs. The age; sex; the shape, location, and size of the ossicle; talofibular articular impingement; and history of major trauma were associated with surgical treatment in statistical analysis. Conclusion: The morphological analysis of the os subfibulare revealed that the ossicle manifested radiographic differences based on its size, location, and morphology. Based on the findings of our study, we suggest it is crucial to understand the morphologeical characteristics of the os subfibulare in patients with CLAI and to establish the treatment plan accordingly.